The echocardiographic determination of volume and muscle mass of the heart - Dickhuth, H. H.; Roecker, K.; Niess, A.; Hipp, A.; Heitkamp, H. C. (International Journal of Sports Medicine, 1997)
One- and two-dimensional echocardiography permits assessment of left ventricular size and muscle mass, whereas the validity and reliability differ. It is comparable to other methods, such as angiography, scintigraphy and magnetic resonance imaging, but has the advantage of being noninvasive and of lower cost. It therefore appears particularly well-suited for applications in sports medicine. However, changes of 10%-20%, depending on the parameter, are necessary in individual cases to permit assumption of a proven change. A further methodical improvement, especially in respect to reliability but also to validity may be expected in the future from three-dimensional, computer-supported examination techniques. Enlargement of the heart due to endurance sports is harmonic and affects all four cardiac chambers. Limits to the increase in left ventricular volume and muscle mass can be recognized in relation to body weight. They usually do not exceed 70% of the baseline value or the value obtained for untrained persons. Power training, even in extreme forms, results in no or only minimal dimensional changes.